Pojmovanje uporabe teorij in modelov zdravstvene nege v klinični praksi - Grmšek Svetlin, Anton (Obzornik zdravstvene nege, 2025)
Introduction: Nursing theories form the knowledge base and theoretical framework for professional practice. The aim of this study was to examine nurses' perceptions of the role and importance of nursing t heories and models in their professional practice and personal development in the clinical setting. Methods: A quantitative, descriptive and non-experimental exploratory empirical method was used. A convenience sample of 110 registered nurses (81 women and 29 men) was collected. The questionnaire consisted of 20 statements related to the perception of the application of nursing theories in clinical practice. The level of statistical significance was set at p ? 0.05. In addition to descriptive statistics, the Mann-Whitney U test, Kruskal-Wallis H test, linear regression and chi-square tests were used for statistical analysis. Results: Respondents expressed a positive attitude towards the role and relevance of nursing theories for their professional practice and personal development (x = 50.02, s = 12.35). The study revealed no statistically significant differences in respondents' regular exposure to information about new nursing theories and models despite their positive attitude to theories and models of nursing. Discussion and conclusion: The data show that nurses are willing to apply nursing theories in clinical practice, but sometimes face problems with the final implementation. It is important for nurses to be aware of the importance of applying nursing theories and models to contribute to better and safer care for all patients.
Keywords: celostna oskrba; integrated care; izobraževanje v zdravstveni negi; kakovost; medicinske sestre; nurses; nursing education; quality